Controlling human corneal stromal stem cell contraction to mediate rapid cell and matrix organization of real architecture for 3-dimensional tissue equivalents. (February 2018) - Mukhey, Dev; Phillips, James B.; Daniels, Julie T.; Kureshi, Alvena K.
Graphical abstract: Abstract: The architecture of the human corneal stroma consists of a highly organized extracellular matrix (ECM) interspersed with keratocytes. Their progenitor cells; corneal stromal stem cells (CSSC) are located at the periphery, in the limbal stroma. A highly organized corneal ECM is critical for effective transmission of light but this structure may be compromised during injury or disease, resulting in loss of vision. Re-creating normal organization in engineered tissue equivalents for transplantation often involves lengthy culture times that are inappropriate for clinical use or utilisation of synthetic substrates that bring complications such as corneal melting. CSSC have great therapeutic potential owing to their ability to reorganize a disorganized matrix, restoring transparency in scarred corneas. We examined CSSC contractile behavior to assess whether this property could be exploited to rapidly generate cell and ECM organization in Real Architecture For 3D Tissues (RAFT) tissue equivalents (TE) for transplantation. Free-floating collagen gels were characterized to assess contractile behavior of CSSC and establish optimum cell density and culture times. To mediate cell and collagen organization, tethered collagen gels seeded with CSSC were cultured and subsequently stabilized with the RAFT process. We demonstrated rapid creation of biomimetic RAFT TE with tunable structural properties. These displayed three distinct regions of varying degrees of cellular and collagen organization. Interestingly, increased organization coincided with a dramatic loss of PAX6 expression in CSSC, indicating rapid differentiation into keratocytes. The organized RAFT TE system could be a useful bioengineering tool to rapidly create an organized ECM while simultaneously controlling cell phenotype. Statement of significance: For the first time, we have demonstrated that human CSSC exhibit the phenomenon of cellular self-alignment in tethered collagen gels. We found this mediated rapid co-alignment of collagen fibrils and thus subsequently exploited this property in vitro to improve the architecture of engineered RAFT tissue equivalents of the corneal stroma. Existing techniques are extremely lengthy and carry significant risk and cost for GMP manufacture. This rapid and tunable technique takes just 8 h of culture and is therefore ideal for clinical manufacture, creating biomimetic tissue equivalents with both cellular and ECM organization. Thus, cellular self-alignment can be a useful bioengineering tool for the development of organized tissue equivalents in a variety of applications.